Case report: Unusual development of hepatocellular carcinoma during immunosuppressive treatments against rheumatoid arthritis overlapping Sjögren’s syndrome; cirrhotic steatohepatitis with liver inflammation and fibrosis lurks in autoimmune disorders - Yoshida, Shuhei; Fujita, Masashi; Ishigame, Teruhide; Kobayashi, Yasuyuki; Sumichika, Yuya; Saito, Kenji; Matsumoto, Haruki; Temmoku, Jumpei; Fujita, Yuya; Matsuoka, Naoki; Asano, Tomoyuki; Sato, Shuzo; et al. (Frontiers in Immunology, 2023)
The sequential progression from chronic liver disease to cirrhosis may be a risk factor for hepatocellular carcinoma (HCC) development. Although HCC originates from hepatitis B virus- or hepatitis C virus-associated liver cirrhosis, it has recently been reported in patients with non-alcoholic steatohepatitis (NASH) with advanced fibrosis. However, little is known about the pathophysiological mechanisms linking HCC to rheumatic disorders, including rheumatoid arthritis (RA). Herein, we describe the case of HCC with NASH complicated by RA and Sjögren’s syndrome (SS). A fifty-two-year-old patient with RA and diabetes was referred to our hospital for further examination of a liver tumor. She received methotrexate (4 mg/week) for 3 years and adalimumab (40 mg/biweekly) for 2 years. On admission, laboratory data showed mild thrombocytopenia and hypoalbuminemia, with normal hepatitis virus markers or liver enzymes. Anti-nuclear antibodies were positive with high titers (x640), and anti-SS-A/Ro (187.0 U/ml; normal range ［NR］: ≤6.9 U/mL) and anti-SS-B/La (320 U/ml; NR: ≤6.9 U/mL) antibodies were also high. Abdominal ultrasonography and computed tomography revealed liver cirrhosis and a tumor in the left lobe (S4) of the liver. She was diagnosed with HCC based on imaging findings, and elevated levels of protein induced by vitamin K absence- II (PIVKA-Ⅱ) were detected. She underwent laparoscopic partial hepatectomy, and histopathological examination revealed steatohepatitis HCC with background liver cirrhosis. The patient was discharged on the 8th day post-operation without any complications. At the 30 months follow-up, no significant evidence of recurrence was observed. Our case suggests that clinical screening for HCC is needed in patients with RA who are at a high risk of NASH, as they may progress to HCC even without elevated liver enzymes.